Creating jobs through public subsidies: an empirical analysis - Sourafel Girma; Holger Görg; Eric Strobl; Frank A. Walsh (Institute for the Study of Labor (IZA), 2007)
This paper analyses the impact of government grants on labour demand using plant level data for manufacturing industry in Ireland. Our data consists of a large sample of plants and their complete grant history. We provide evidence that additional employment is created over and above the level that would have prevailed in the absence of grant payments. We also find differences in the employment response to subsidies between domestic and foreign-owned plants, with the former creating more additional jobs per euro of grant payment. Simple cost-benefit analysis reveals that a large part of the costs of grants appears to be recouped in additional wage streams under reasonable assumptions. – Grants ; labour demand ; multinationals
Keywords: H25; 330; Arbeitsnachfrage; Subvention; Wirtschaftspolitische Wirkungsanalyse; Beschäftigungseffekt; Irland